Characterisation of three alpha-helical antimicrobial peptides from the venom of Scorpio maurus palmatus. (July 2016) - Harrison, Patrick L.; Abdel-Rahman, Mohamed A.; Strong, Peter N.; Tawfik, Mohamed M.; Miller, Keith
Abstract: Scorpion venoms provide a rich source of anti-microbial peptides. Here we characterise three from the venom of Scorpion maurus palmatus . Smp13 is biologically inactive, despite sharing homology with other antimicrobial peptides, probably because it lacks a typically charged structure. Both Smp-24 and Smp-43 have broad spectrum antimicrobial activity, disrupting bacterial membranes. In addition, there is evidence that Smp24 may inhibit DNA synthesis in Bacillus subtilis. Smp24 haemolysed red blood cells but in contrast, Smp43 was non-haemolytic. The introduction of a flexible Gly-Val-Gly hinge into the middle of Smp24 did not alter the haemolytic activity of Smp24 (as might have been predicted from earlier studies with Pandinin2 (Pin2), although C-terminal truncation of Smp-24 reduced its haemolytic activity, in agreement with earlier Pin 2 studies. Smp24 and its derivatives, as well as Smp-43, were all cytotoxic (ATP release assay) toward mammalian HepG2 liver cells. Our results highlight the beneficial effect of helical-hinge-helical conformation on promoting prokaryotic selectivity of long chain scorpion AMPs, as well as the importance of examining a wide range of mammalian cell types in cytotoxicity testing. Highlights: Three antimicrobial peptides were derived from the venom of Scorpio maurus palmatus . Two of these peptides, Smp24 and Smp43, have promising membrane disruptive activities. A hinge-helical-hinge conformation promotes prokaryotic specificity in scorpion-derived antimicrobial peptides.